Plan de mantenimiento general para los tableros de control de una bomba de inyección de agua en pozos de crudo (2022)
The proposal of a maintenance plan for the control boards of the water injection pump used in crude oil wells is proposed; given that there is no frequency of inspection and review of the electrical and mechanical components involved that include specific preventive maintenance activities that cover the equipment, instruments and other components of the panels, thus allowing the maintenance frequencies to be determined since there are no maintenance plans maintenance that integrates the drive control boards, TBT (low voltage board) and instrumentation control board.